Preserving MSMEs Competitive Advantage: Moderation by Business Size - Norvadewi Norvadewi; Akhmad Nur Zaroni (JASF: Journal of Accounting and Strategic Finance, 2024)
One business sector that has the biggest impact on the expansion of the national economy is Micro, Small, and Medium Enterprises (MSMEs). Due to the economic crisis, some MSMEs have developed successfully, while others have failed. This study analyzes the influence of entrepreneurial leadership, digital marketing, and HR competence on MSMEs' competitive advantage, with business size as a moderating variable. This study uses quantitative methodology and a causal associative approach. The stratified random sampling technique ensured adequate representation from diverse industries and geographic regions. A questionnaire distributed and completed by 150 MSME entrepreneurs in Nunukan, Berau, and Kutai Kartanegara, East Kalimantan Province, was used to gather data. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to analyze the data. The study showed that entrepreneurial leadership and digital marketing significantly affect MSME's competitiveness. Meanwhile, HR competence and business size have an insignificant effect on MSMEs' competitive advantage in East Kalimantan Province. Business size is proven to moderate the effect of entrepreneurial leadership and digital marketing on MSMEs' competitive advantage in East Kalimantan Province. The business size cannot moderate the relationship between HR competence and MSMEs' competitive advantage. The results of this research can serve as a guide for future researchers who will tackle related issues. The study is anticipated to act as a mutually beneficial role model to guarantee the best possible empowerment of MSMEs with the aid of technology.